The THE EXPERIENCE OF TYPE 2 DIABETES MELLITUS MALE PATIENTS WHO UNDERGO SEXUAL DYSFUNCTION - Imelda Sirait; Setiawan Setiawan; Rosina Tarigan (International Journal of Nursing and Health Services (IJNHS), 2019)
The sexual problem became a sensitive issue and embarrassed among patients, especially among those who are living with diabetes. The study aimed to dig up deeply the experience of male patients with diabetes mellitus type 2 who underwent sexual dysfunction. The qualitative study with phenomenology approach was applied in this study. We collected the data by using an interview method. Fifteen samples were recruited using the purposive sampling technique and selected from Endocrine Polyclinic Martha Friska Hospital. The interview transcriptions were analyzed using the qualitative content analysis approach. Four themes related to the patients’ experience on sexual dysfunction have been analyzed in this study including 1) feeling that the sexual libido was high in the midst of the limitation of sexual dysfunction, 2) inferior feelings toward mates, 3) attempting to adapt to sexual changes, 4) trying to solve sexual problems in different ways. The participant had bad experience wich influence their quality of life with their partner. We suggested to the health care providers, including doctors, nurses, etc. to design the cultural program for addressing the sexual problem and completed the facilities for sexual favors. Keywords: type 2 diabetes mellitus, Experience, sexual dysfunction